Exergy-based control strategies for the efficient operation of building energy systems. (20th December 2019) - Sayadi, Saeed; Tsatsaronis, George; Morosuk, Tatiana; Baranski, Marc; Sangi, Roozbeh; Müller, Dirk
Abstract: This article addresses the merits of exergy-based control strategies in comparison to energy-based ones in terms of increasing the energetic efficiency of a building and/or decreasing the operating costs of Heating, Ventilation and Air Conditioning (HVAC) systems. In this study, a dynamic exergy model for building energy systems is demonstrated to calculate exergy destruction which is a true measure of thermodynamic inefficiencies in a system. The exergy-based control strategies minimize exergy destruction obtained from the building exergy model while satisfying thermal comfort constraints. In this way, HVAC systems operate in a low-exergy fashion. The results of this study show that the implementation of exergy-based control strategies reduces the quality mismatch between energy supply and demand, and therefore, increases the sustainability of building energy systems. To prove the practicability of the idea, application of exergy-based control strategies in different types of case studies is investigated. The first case study deals with the design of optimal local controllers for the end-users without considering the entire energy supply chain. It is shown that the total operating cost of the system can be decreased by 13% through the implementation of an exergy-based control strategy. The second case study proposes an exergy-based control algorithm that, in addition to the end-users, also considers the upstream components and sub-systems in the energy supply chain. This control algorithm has been tested in a part of the heating system in the main building of the E.ON Energy Research Center (ERC), and the results shows that the proposed control strategy is sufficiently fast and the mass flow rates inside the consumer circuits are relatively stable. The third case study demonstrates a large-scale application, in which an Exergy-based Linear Model Predictive Controller (ExLiMPC) is implemented in a dynamic model representing the working principles of the HVAC and control systems of the main building of the E.ON ERC. A comparison between the default controller and the ExLiMPC shows that the ExLiMPC is able to decrease the overall energy demand of the building by 23.1%.